2013
DOI: 10.2807/1560-7917.es2013.18.42.20609
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant tuberculosis in Uzbekistan: results of a nationwide survey, 2010 to 2011

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…Ndung'u et al 8 showed 66.5% of the MDR-TB study population in Nairobi were unemployed and 79.4% earned less than 100 USD per month. MDR-TB estimates for Uzbekistan were among the highest reported in former Soviet Union countries which were attributed to factors like imprisonment, unemployment and previous treatment with TB as shown by Ulmasova et al 7 . Primarily resistant TB strains, malnutrition, poverty, overcrowding, poor hygiene, decreased health care seeking attitude formed a vicious cycle of agent-host-environment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ndung'u et al 8 showed 66.5% of the MDR-TB study population in Nairobi were unemployed and 79.4% earned less than 100 USD per month. MDR-TB estimates for Uzbekistan were among the highest reported in former Soviet Union countries which were attributed to factors like imprisonment, unemployment and previous treatment with TB as shown by Ulmasova et al 7 . Primarily resistant TB strains, malnutrition, poverty, overcrowding, poor hygiene, decreased health care seeking attitude formed a vicious cycle of agent-host-environment.…”
Section: Discussionmentioning
confidence: 94%
“…A study in west Australia by Francis et al 6 showed the median age of the MDR-TB patients were 26 years. However, in separate studies Ulmasova et al 7 and Ndung'u et al 8 showed that MDR-TB was significantly associated with age less than 45 years in Uzbekistan and Nairobi (88.7%) respectively. Malnutrition since childhood leading to weakened immune response, made the younger population more susceptible to MDR-TB in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some settings, mainly located in Eastern Europe and Central Asia, the proportions are further amplified (up to 50% versus 20%, respectively) [1,[6][7][8]. The detection capacity increased between 2011 and 2012 (42%); although, unfortunately it was not followed by an increased treatment capacity.…”
mentioning
confidence: 99%
“…However, in some settings (Eastern Europe and Central Asia), the proportions are further amplified to reach 50% [15][16][17][18].…”
mentioning
confidence: 97%